Rheumatologic diseases as the cause of fever of unknown origin. Issue 5 (October 2016) - Mulders-Manders, C.M.; Simon, A.; Bleeker-Rovers, C.P.
Abstract: In 30% of patients with fever or inflammation of unknown origin (FUO/IUO), the cause is eventually found to be a rheumatologic disease such as autoimmune or granulomatous disease or vasculitis. Most of these patients suffer from an uncommon presentation of a common disease, instead of an uncommon disease. We demonstrate the diagnostic challenge with several cases. The workup of FUO is based on the identification of potential diagnostic clues (PDCs). In the absence of PDCs, a standardized diagnostic protocol should be followed, including early FDG–PET/CT. Other imaging techniques or invasive diagnostic techniques should be reserved for those in whom PDCs are present.